A Majalah Sains Tentang Uji Fitokimia dari Ekstrak Daun Peluntan (Artocarpus Sericicarpus) - Aliefman Hakim; Muti'ah Muti'ah; Senly Apriani (Chemistry Education Practice, 2026)
This study aims to create a magazine and determine the level of validity and response of readers of science magazines regarding phytochemical tests of peluntan leaf extract (Artocarpus sericicarpus) as student reading material. This study is a research and development (RnD) with a 4D model (Define, Design, Development, and Dissemination). The validators for this science magazine are two lecturers of Chemistry Education. The research sample consisted of 30 students of the Chemistry Education Study Program who were selected using a purposive sampling technique and collected through a response questionnaire. Validation data were processed using the Aiken's V formula, while the magazine trial based on student responses was processed using the percentage formula. The validity results showed an average value of Aiken's V = 0.92, which is classified as very valid. The science magazine trial produced a value of 92.5%, which is classified as very useful. Based on these results, it can be concluded that the science magazine developed is very valid and useful for use as reading material. This research is expected to contribute to the development of useful reading materials in the field of Chemistry Education.